Dealing with foreign cultural paradigms: A systematic review on intercultural challenges of international medical graduates. - Kerstin Michalski; Nabeel Farhan; Edith Motschall; Werner Vach; Martin Boeker (PLoS ONE)
Objectives An increasing number of International Medical Graduates (IMG), who are defined to be physicians working in a country other than their country of origin and training, immigrate to Western countries. In order to ensure safe and high-quality patient care, they have to take medical and language tests. This systematic review aims to (1) collect all empiric research on intercultural communication of IMGs in medical settings, (2) identify and categorize all text passages mentioning intercultural issues in the included studies, and (3) describe the most commonly reported intercultural areas of communication of IMGs. Methods This review was based on the PRISMA-Guidelines for systematic reviews. We conducted a broad and systematic electronic literature search for empiric research in the following databases: MEDLINE, BIOSIS Citation Index, BIOSIS Previews, KCI-Korean Journal Database and SciELO Citation Index. The search results were synthesized and analyzed with the aid of coding systems. These coding systems were based on textual analysis and derived from the themes and topics of the results and discussion sections from the included studies. A quality assessment was performed, comparing the studies with their corresponding checklist (COREQ or STROBE). Textual results of the studies were extracted and categorized. Results Among 10,630 search results, 47 studies were identified for analysis. 31 studies were qualitative, 12 quantitative and 4 studies used mixed methods. The quality assessment revealed a low level of quality of the studies in general. The following intercultural problems were identified: IMGs were not familiar with shared decision-making and lower hierarchies in the health care system in general. They had difficulties with patient-centered care, the subtleties of the foreign language and with the organizational structures of the new health care system. In addition, they described the medical education in their home countries as science-oriented, without focusing on psychosocial aspects. Conclusion There is a need for a better training of IMGs on culture-related and not culture-related topics in the new workplace country. The topics that emerged in this review constitute a basis for developing these courses. Further empiric research is needed to describe the findings of this review more precisely and should be in accordance with the existing reporting guidelines.